Legalizing Oral History: Proving Aboriginal Claims in Canadian Courts - McNeil, Kent; Roness, Lori Ann (Osgoode Digital Commons, 2000)
Large areas of Canada are still subject to land claims by the Aboriginal peoples, who include the Indian, Inuit, and Metis. These claims arise mainly in regions where land-surrender treaties were not signed in the past, notably in British Columbia, Quebec, the Atlantic Provinces, and the North. Most of them get resolved through negotiation and agreement, but a few end up in court. When that happens, the onus is on the Aboriginal peoples to prove their claims in accordance with the requirements of the Canadian legal system. This article will examine some of the difficulties Aboriginal peoples encounter when they rely on their oral histories for this purpose.